2019
DOI: 10.1152/ajplung.00169.2018
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol modulates the signaling of chemosensory bitter taste receptor T2R14 in human airway cells

Abstract: Bitter taste receptors (T2Rs) are a group of 25 chemosensory receptors expressed at significant levels in the human airways. In human airways, bitter taste receptor 14 (T2R14)-mediated physiological response in ameliorating obstructive airway disorders is an active area of investigation. Therefore, understanding various factors regulating the structure and function of T2R14 will be beneficial. We hypothesize that membrane lipids like cholesterol play a regulatory role in T2R14 signaling in airway cells. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Membrane remodelling, a prerequisite for acrosome reaction, is induced by cholesterol efflux, that alters lipid raft stability and distribution, favours specific protein-protein interactions by concentrating certain proteins in specific microdomains while excluding others. The physiological cholesterol efflux seems to play a regulatory role on taste receptors through the CRAC motif, influencing TasRs signalling efficacy, as reported in human airway cells [99].…”
Section: Taste Receptors In Epididymal Maturation and Sperm Functionmentioning
confidence: 95%
“…Membrane remodelling, a prerequisite for acrosome reaction, is induced by cholesterol efflux, that alters lipid raft stability and distribution, favours specific protein-protein interactions by concentrating certain proteins in specific microdomains while excluding others. The physiological cholesterol efflux seems to play a regulatory role on taste receptors through the CRAC motif, influencing TasRs signalling efficacy, as reported in human airway cells [99].…”
Section: Taste Receptors In Epididymal Maturation and Sperm Functionmentioning
confidence: 95%
“…All the GECs were cultured in serum free KGM‐2 supplemented with 0.6mM CaCl 2 . HEK293T and HEK293T cells overexpressing T2R14 and T2R39 receptor were generated as previously described 24 . The promyeloblast (HL‐60) cells were cultured in IMDM supplemented with 20% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…The intracellular calcium mobilization (Ca 2+ )i upon agonist stimulation was measured using calcium binding fluorescent dye Fluo-4NW as described previously [17,24]. Briefly, GECs (3x10 /well) and HEK293T cells stably over-expressing T2R14 or T2R39 (1x10 5 /well each) were seeded in a black well 96-well BD optilux plate and grown overnight to full confluency.…”
Section: Intracellular Calcium Mobilization Assaymentioning
confidence: 99%
“…A comparison of the dynamics of wild-type T2R14 receptors and mutant T2R14 receptors revealed that the amino acid residues K110, F236, and L239 are required for the receptor to function appropriately when cholesterol is present. Based on this study, it could be suggested that cholesterol influences taste receptors by directly interacting with the receptor [ 165 ].…”
Section: Significance and Interaction Sites Of Cholesterol In Class C...mentioning
confidence: 99%